PEMBUATAN LILIN AROMATERAPI DENGAN PENAMBAHAN MINYAK JERUK MANIS DI DUSUN SERI, DESA URIMESSING, KOTA AMBON - Grace Sipahelut, Sophia; Mailoa, Meitycorfrida; C. D. Tuhumury, Helen (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2022)
The main purpose of this community service activity is to increase the knowledge and skills of the community in making aromatherapy candles with the addition of sweet orange essential oil in Dusun Seri, Urimessing Village, Nusaniwe District, Ambon City. The target of this activity is the community of Dusun Seri, Urimessing Village, while the methods used are counseling, training/practice and evaluation. Based on the results of observations and questionnaires, there was an increase in public knowledge about the efficacy of aromatherapy candles, the benefits of essential oils, and the technique of making essential oil-based aromatherapy candles. The public received new information about the use of aromatherapy candles as an easy and inexpensive relaxation medium. In addition, the community has new skills in making aromatherapy candles made from the aroma of sweet orange essential oil. Through this activity, it can also improve public health because by inhaling the aroma of aromatherapy candles, it will make the mind calm and reduce anxiety. This service activity was able to motivate participants to make aromatherapy candles for use with their families. Participants were very enthusiastic about this activity from beginning to end.